PENGARUH EKSPOR TERHADAP PERTUMBUHAN EKONOMI DI PROVINSI SULAWESI TENGGARA - Teguh Permana; Andriani Puspitaningsih; Surianti Surianti; Wa Ode Rachmasari Ariani (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2024)
This research aims to determine the effect of exports on economic growth. The data used is secondary data originating from BPS Southeast Sulawesi publications for 2004-2023. This research uses quantitative research with simple regression analysis. The research results show that exports have an insignificant effect on economic growth with a negative relationship. This shows that when exports increase, economic growth tends to decrease, and conversely, when exports decrease, economic growth tends to increase. This is not in accordance with theory, but previous research in different locations found the same thing. Another factor that causes a negative relationship is the Covid19 pandemic. The implication of this research is that there must be an increase in the use value of exported goods, meaning there must be factories that process raw goods into finished goods which can provide a multiplier effect and have a positive impact on economic growth.